Aberrant synaptic input to retinal ganglion cells varies with morphology in a mouse model of retinal degeneration. Issue 18 (18th August 2014) - Yee, Christopher W.; Toychiev, Abduqodir H.; Ivanova, Elena; Sagdullaev, Botir T.
ABSTRACT Retinal degeneration describes a group of disorders which lead to progressive photoreceptor cell death, resulting in blindness. As this occurs, retinal ganglion cells (RGCs) begin to develop oscillatory physiological activity. Here we studied the morphological and physiological properties of RGCs in rd1 mice, aged 30–60 days, to determine how this aberrant activity correlates with morphology. Patch‐clamp recordings of excitatory and inhibitory currents were performed, then dendritic structures were visualized by infusion of fluorescent dye. Only RGCs with oscillatory activity were selected for further analysis. Oscillatory frequency and power were calculated using power spectral density analysis of recorded currents. Dendritic arbor stratification, total length, and area were measured from confocal microscope image stacks. These measurements were used to sort RGCs by cluster analysis using Ward's Method. This resulted in a total of 10 clusters, with monostratified and bistratified cells having five clusters each. Both populations exhibited correlations between arbor stratification and aberrant inhibitory input, while excitatory input did not vary with arbor distribution. These findings illustrate the relationship between aberrant activity and RGC morphology at early stages of retinal degeneration. J. Comp. Neurol. 522:4085–4099, 2014. © 2014 Wiley Periodicals, Inc.